Study of Catalysts Deactivation in Isomerization Process to Produce High Octane Gasoline - A. Sukkar, Khalid; M. Abdul-Raheem, Hayam; Th. Juber, Amel; Sh. Jumaly, Jabir (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
In this study the isomerization of desulfuerized light Iraqi petroleum naphtha (Al-Dura Refinery) with boiling point range of 37 to 124 °C , 80.5 API specific gravity and 68.2 octane number has been investigated. Two types of catalysts were prepared (Pt/HX and Pt/SrX) by impregnation of 0.8 wt% Pt on l 3X-zeolite. The catalyst activity and selectivity toward isomerization, and catalyst deactivation were investigated. The isomerization unit consisted of a vertical tubular stainless steel reactor of 2 cm internal diameter, 3 cm external diameter and 68 cm height. The operating pressure was atmospheric for all experimental runs. The liquid flow of lightnaphtha was 0.4 Uh, and the catalyst weight was 50 gm, H/ H.C ratio used was 4 for all experimental runs. The isomerization process was studied at different temperatures of 250, 270, 275, 300, 325, and 350 °C . It was found that, the optimum isomerization temperature is 270 °C. The isomerization activities and selectivities as a function of time showed high activity at the beginning of the reaction and were deactivated rapidly. This indicates that the deactivation of Pt/HX and Pt/SrX results from the blocking of pore mouth by the deposited carbon. The following deactivation decreasing order, Pt/HX > Pt/SrX was found. On the other hand, Pt/HX catalyst shows higher activity and selectivity than that of Pt/SrX It was concluded that, only an average o/ 90 wt% of the carbon atoms feed into the reactor (light naphtha) is detected " the product stream due to formation of coke deposits which leads to catalyst deactivation. The results clearly showed 1at hydrogen is necessary for the hydrogenation of olefins in order to prevent oligomerization reaction that leads to coke formation and catalyst deactivation.